Simultaneous achievement of energy recovery and carbon sequestration through municipal solid waste management: A review - Salvador, Ruben W.; Doong, Ruey-An (Chemosphere (Oxford), 2024)
Effective municipal solid waste (MSW) management is a crucial component for sustainable cities, as inefficient waste disposal contributes to the release of about a billion tons of CO2-eq in greenhouse gases (GHG) annually. With escalating global waste generation, there is an untapped opportunity to integrate carbon dioxide removal (CDR) technologies into existing MSW management processes. This review explores current research on utilizing MSW for CDR, emphasizing its potential for both energy generation and carbon sequestration. The investigation covers three waste management practices: landfilling, waste-to-energy (WtE), and biochar production, revealing two paths for carbon sequestration. First, MSW serves as a feedstock in bioenergy with carbon capture and storage (BECCS), acting as a carbon-neutral resource that avoids fossil fuel and energy crop use, reducing GHG emissions and generating value through energy production. Second, direct storage of organic MSW and its derivatives, like biochar, in various carbon sinks allows for extended sequestration, offering a comprehensive approach to address the challenges of waste management and climate change mitigation. Moreover, this review advocates for an extended exploration into several subjects including in-depth analysis of waste, research on MSW-derived biochar recalcitrance across different carbon sinks, and understanding the symbiotic connections with GHG-emitting sectors like agriculture and energy. Finally, this review emphasizes the necessity of conducting life-cycle assessment studies to fully discern the benefits and assess the impacts of any future endeavors exploring the role of MSW in carbon sequestration. [Display omitted] •Municipal solid waste (MSW) is an untapped resource for carbon dioxide removal.•Three strategies to utilize MSW for CO2 removal include landfilling, waste-to-energy, and biochar production.•Carbon sequestration is achieved through MSW-burial and energy recovery with CCS.•Auditing carbon emissions and LCA are necessary to illuminate the impacts of MSW.